Sport Coaching and Development Policy: A Case Study in Rock Climbing Sports - Hartadji, Herdi; Ma’mun, Amung; Hendrayana, Yudy; Juliantine, Tite (Indonesian Journal of Sport Management, 2023)
This study aims to provide an idea to the government that the importance of rock climbing should be developed in every city / district. With the aim of the government, it must be able to develop a rockclimbing sport because rock climbing has many benefits for those who do it. Rock climbing is a sport that develops due to the large number of enthusiasts only to improve physical condition, psychology or enthusiasts in achieving achievements, improving the physical condition that can be achieved in rock climbing such as increased strength, power, flexibility, balance and hand eye coordination. Psychological improvement is seen from the increase in self-confidence, motivation and concentration. In the current decade, Indonesian rockclimbing athletes have made an extraordinary history because they have been able to compete with other countries in every championship / event by getting gold medals, for this sport infrastructure does not require expensive equipment or extensive field because this sport is only need a climbing wall and climbing equipment that the price is still affordable. This research method uses literature review. The articles used in this literature review are articles obtained using 3 databases of Taylor and Francis, Google Scholar and Science Direct which support the research. It is hoped that this research can provide a clear picture for the government in making rock climbing development policies in every city / district